Development of a sustainable bioprocess based on green technologies for xylitol production from corn cob - Sara Baptista (2020)
In this work, a sustainable and environmental friendly strategy for the biotechnological production of xylitol was proposed and optimized. For this purpose, corn cob was hydrothermally pretreated at high solid loadings (25%) for an efficient solubilization of xylan in hemicellulose derived compounds, xylooligosaccharides and xylose. Xylose enriched streams were obtained from the enzymatic saccharification of the whole slurry (solid and liquid fraction) resulting from the autohydrolysis pretreatment. The xylitol production in a simultaneous saccharification and fermentation (SSF) process, by the recombinant Saccharomyces cerevisiae PE-2-GRE3 strain, was optimized using different enzyme and substrate (pretreated corn cob solid) loadings by an experimental design. This study demonstrated a significant effect of substrate loading on the production process achieving a maximal concentration of 47g/L with 6.7 % of pretreated corn cob and 24 FPU/g of enzyme loading, with partial detoxification of the hydrolysate. Furthermore, the 1.42-fold increase in xylitol titer and 1.56-fold increase in productivity achieved in a SSF using an acetic acid free-hydrolysate evidenced the negative effect of acetic acid on the yeast-based xylitol production process. The combination of these green technologies and the optimization of the proposed strategy enhanced the overall xylitol production through the valorization of corn cob.